Effect of the Iridoid-rich Fraction from Valeriana jatamansi Jones on Oxidative Stress in Rats with Spinal Cord Injury - Jiaojuan HUANG; Wenchun WANG; Deqi XIONG; Hao LU; Wu XIANG; Xiaohua ZHAO; Ruihan ZHOU; Anren ZHANG (康复学报)
Objective:To investigate the effects of iridoid-rich fraction from Valeriana jatamansi Jones on oxidative stress in rats with spinal cord injury(SCI)from the histological and molecular biological levels.Methods:A total of sixty male Sprague-Dawley rats weighing(250±30)g were randomly divided into three groups(20 rats per group):the sham-operated group, the model group, and the treatment group with 10 mg/kg iridoid-rich fraction from Valeriana jatamansi Jones. The model of SCI was established by a medical aneurysm clip, the sham-operated group was only performed by laminectomy without injuring the spinal cord. Two hours after model establishment successfully, the treatment group was given iridoid-rich fraction from Valeriana jatamansi Jones by intragastrical administration with 10 mg/kg, and the sham-operated group and the model group were given an equal volume of sodium carboxymethylcellulose(CMC-Na)solution with the same way. And each of groups was given intragastrical administration once a day. The rats were sacrificed on third days after administration, and the contents of oxidative stress indexes superoxide dismutase(SOD)and malondialdehyde(MDA)in serum were detected by enzyme linked immunosorbent assay(ELISA); the related biochemical kit was used to test glutathione peroxidase(GSH-PX)and catalase(CAT)viability of the spinal cord tissue; the expression levels of apoptosis-related proteins of Caspase-3, B cell lymphoma(Bcl-2)associated X protein(Bax), and Bcl-2 were detected by Western blot; and the Hematoxylin/eosin(HE)staining was used to observe the pathological changes of the spinal cord tissue at the perilesional area; and Terminal-deoxynucleoitidyl transferase mediated nick end labeling(TUNEL)was used to observe the apoptosis of nerve cells of the spinal cord tissue at the perilesional area.Results:The results of ELISA showed that compared with the sham-operated group, the SOD content in the serum of the model group decreased, and the MDA content increased; compared with the model group, the SOD content in the serum of the treatment group with iridoid-rich fraction from Valeriana jatamansi Jones increased significantly(P< 0.05), and the MDA content decreased significantly(P< 0.01). The results of the biochemical kit tests showed that the activity of GSH-PX and CAT antioxidant enzymes in the spinal cord of the model group was lower than that in the sham-operated group; compared with the model group, in the treatment group with iridoid-rich fraction from Valeriana jatamansi Jones the activity of the antioxidant enzymes of GSH-PX(P< 0.05)and CAT(P< 0.01)of the spinal cord tissue increased significantly. The Western blot results showed that compared with the sham-operated group, the expression of pro-apoptosis protein increased and the anti-apoptotic protein decreased in the model group; compared with the model group, the expression of pro-apoptotic protein(Caspase-3 and Bax)decreased significantly(P< 0.05), and the expression of anti-apoptotic protein(Bcl-2)increased significantly(P< 0.05), and simultaneously, the proportion of Bax/Bcl-2 decreased significantly(P< 0.01)in the treatment group. The results of the HE staining showed that the structure of gray matter and white matter of the spinal cord tissue in the sham-operated group were normal at the perilesional area, the structure of the neurons was also clear, and no significant spinal cord injured was found; compared with the sham-operated group, the spinal cord structure was severely damaged in the model group: the gray matter of the central part of the spinal cord and the white matter of the surrounding part of the spinal cord turned into blur because of injury and a large number of neurons degenerated, a number of nerve cells even appeared necrosis, and the cell structure was seriously destroyed at the same time, and in addition, the nuclear turned into shrinkage or dissolution and passed away, accompanying with varying degrees of neutrophil infiltration and a large number of microglia proliferation; compared with the model group, the spinal cord structure of the treatment group with iridoid-rich fraction from Valeriana jatamansi Jones significantly improved, and there were only small areas presenting a neuronal necrosis, a small amount of eosinophils increasing and a small number of eosinophils microglia infiltration in the spinal cord tissue at the perilesional area, and at the same time, the histopathological scores in tissue sections were lower(P< 0.05). The results of the TUNEL method showed that there were not obvious brown-yellow nerve apoptotic cells in the spinal cord tissue of the sham-operated group, and, however, there were obvious brown-yellow apoptotic nerve cells in the spinal cord tissue at the perilesional area of the model group; compared with the model group, the number of brown-yellow apoptotic nerve cells in the treatment group with iridoid-rich fraction from Valeriana jatamansi Jones attenuated apparently(P< 0.05).Conclusion:The iridoid-rich fraction from Valeriana jatamansi Jones has neuroprotective effects on rats with spinal cord injury, and its mechanism may be related to the reduction of oxidative stress after SCI.